RETRACTED: Chemical composition of helichrysum maracandicum popov ex kirp. in the condition in vitro cultivated - Tashpulatov Y.Sh.; Sarabekov A.T.; Khasanov N.S.; Valiyev Sh.A.; Khujanov A.N. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001